Efek Komunikasi Massa Pada Khalayak (Studi Deskriptif Pengguna Media Sosial dalam Membentuk Perilaku Remaja - Fifit Fitriansyah (Cakrawala - Jurnal Humaniora, 2018)
The phenomenon of online media such as social media, currently has provided support for massive social interaction and organized. The role of social media that has used web-based technology has now transformed communication into an interactive dialogue. Some of the popular social media currently include instagram, facebook, Twitter, youtube, and vlog. While the effect of mass communication (cognitive, affective and behavioral) for users or social media audiences in which case adolescents have changed their behavior, both positively and negatively. This study focuses on how the effect of mass communication on audiences that use social media that in fact is a teenager. Where adolescence is a period of transition between childhood and adulthood. As a result of this transition, then what he knows, he feels it will be reflected through his behavior.